The effect of systemic zinc supplementation on oral health in low socioeconomic level children - Uçkardeş, Yasemin; Tekçiçek, Meryem; Ozmert, Elif N; Yurdakök, Kadriye (The Turkish Journal of Pediatrics, 2009)
There is limited evidence about the effects of systemic zinc supplementation on oral health in healthy children. The aim of this study is to determine the effect of oral zinc supplementation on oral health in low socioeconomic level primary school children. In this double-blind randomized study, 68 children were randomly separated into two groups (study and placebo) to receive 15 mg/day elemental zinc or placebo syrup five days a week for 10 weeks. Oral examinations were performed before and after supplementation. After supplementation, the Gingival Index improved statistically in both groups (p < 0.05). However, the Plaque Index improved statistically only in the zinc group (p = 0.02). After supplementation, the Plaque Index scores increased in 13 cases and decreased in 15 in the placebo group (p = 0.70) and increased in only 6 cases and decreased in 18 in the study group (p = 0.02). Oral zinc supplementation may contribute to the prevention of dental caries in low socioeconomic level primary school healthy children.